2019
DOI: 10.1016/j.ceb.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Actin-dependent endosomal receptor recycling

Abstract: Endosomes constitute major sorting compartments within the cell. There, a myriad of transmembrane proteins (cargoes) are delivered to the lysosome for degradation or retrieved from this fate and recycled through tubulo-vesicular transport carriers to different cellular destinations. Retrieval and recycling are orchestrated by multi-protein assemblies that include retromer and retriever, sorting nexins, and the Arp2/3 activating WASH complex. Fine-tuned control of actin polymerization on endosomes is fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 105 publications
(200 reference statements)
5
109
0
Order By: Relevance
“…First, Arp2/3 may act at the endosome to promote anterograde sterol transfer, such that its inhibition leads to a retention of sterols in endosomes. In support of this, Arp2/3 is well-established to localize to endosomes and play numerous roles in cargo sorting and membrane fission in mammalian cells (Simonetti and Cullen, 2019). The spherical shape of STRIC post CK-666 treatment, which contrasts with the more varied shapes of Syb1-positive organelles in untreated cells, also suggests that Arp2/3dependent actin nucleation may contribute to membrane deformation on the endosome also in yeast cells.…”
Section: Why Does Arp2/3 Inhibition Lead To Sterol Accumulation In Enmentioning
confidence: 81%
“…First, Arp2/3 may act at the endosome to promote anterograde sterol transfer, such that its inhibition leads to a retention of sterols in endosomes. In support of this, Arp2/3 is well-established to localize to endosomes and play numerous roles in cargo sorting and membrane fission in mammalian cells (Simonetti and Cullen, 2019). The spherical shape of STRIC post CK-666 treatment, which contrasts with the more varied shapes of Syb1-positive organelles in untreated cells, also suggests that Arp2/3dependent actin nucleation may contribute to membrane deformation on the endosome also in yeast cells.…”
Section: Why Does Arp2/3 Inhibition Lead To Sterol Accumulation In Enmentioning
confidence: 81%
“…By binding to WASP proteins, ITSN2-L facilitates Cdc42-dependent actin polymerization (Klein et al, 2009;McGavin et al, 2001). Actin polymerization may act as a scaffold to limit cargo diffusion on endosomes and control their fate (Simonetti and Cullen, 2019). In contrast to Cdc42, RhoU does not interact with the GTPase binding domain of WASP (Saras et al, 2004) and among RhoU effector, none has been reported to mediate actin polymerization.…”
Section: Our Findings Question Whether Rhou Activities Might Be Regulmentioning
confidence: 99%
“…Dynamic rearrangement of the actin cytoskeleton is a critical component in generating tubular membrane systems (Gautreau et al, 2014;Simonetti and Cullen, 2019) . It relies on the capacity of actin filaments to polymerize and depolymerize, a characteristic that can be influenced by the ability of DBN to bind the lateral filament surface, to bundle actin filaments and to inhibit actin nucleation (Ginosyan et al, 2019;Grintsevich et al, 2010;Li et al, 2019).…”
Section: Dbn Generates Tubular Endosomes By Counteracting Arp2/3-depementioning
confidence: 99%
“…Membrane tubulation occurs particularly on maturing early endosomes and macropinosomes to separate components from the quick 'bulk flow' back to the plasma membrane and to direct them towards other compartments such as the Golgi network or recycling endosomes (Naslavsky and Caplan, 2018). The actin cytoskeleton creates stable tubular subdomains, where membrane-bound cargos segregate and concentrate according to their designated destinations (Bowman et al, 2016;Puthenveedu et al, 2010;Simonetti and Cullen, 2019). We propose a role for DBN in inwarddirected RAB8-based membrane trafficking: upon wounding, DBN may contribute to the uptake of plasma membrane material by compiling endocytosed receptors and material in the injury-induced RAB8-compartment that are essentially sorted by DBN-stabilized tubules ( Figure 7).…”
Section: Dbn Functions As An Injury-induced Actin Regulator In Membramentioning
confidence: 99%